A gestão da educação pública em disputa em Goiás: uma análise discursiva da cobertura midiática do acontecimento das OS’s (2015 – 2017) - Souza, Fábio Márcio Gaio de (2022)
This doctoral thesis in Letters and Linguistics aimed to analyze the statements of the journalistic media about the management of state elementary and high schools in Goiás by Social Organizations (OSs). To this end, we consider the process as an event and ask what made possible, in the journalistic media, the emergence of these statements that tried to transfer the management of school institutions from teachers to SOs. For those institutions that were proposing, was enough only the schools were managed by Principals-Managers. Based on Michel Foucault's theoretical foundations and solutions, a basis for reflection, in dialogue with the theory of communication and journalism, we questioned about the vaunted and we were able to verify the existence of rules that allowed the emergence of the relationship between uncertainty and security ensured by the current model and the supposed certainty and security by supposedly professional management. This articulation, based on an economic rationality and neoliberal market, was considered one of the main strategies and alleged reason for implementing the new model. To us, the governmental utterances reproduced by midia, with few exceptions, were in successive coadunation with the government expectations, related to the project’s success, had consisted of the deconstruction attempt and silencing of the opposites. Attempts to escape this technology of government represented by SOs, both in the media and in life, although narrow and restricted, represented the firm refusal of these technologies and the possibility of new forms of government of oneself and others. This articulation, based on neoliberal economic and market rationality, was considered one of the main strategies and alleged reason for implementing the new model. For us, the statements produced by the government and reproduced by the media were, with few exceptions, in line with government expectations regarding the success of the project and, not only that, they consisted of successive attempts at deconstruction and silencing the opposites. Attempts to escape this technology of government represented by SOs, both in the media and in life, although narrow and restricted, represented the firm refusal of these technologies and the possibility of new forms of government of oneself and others.